Про окремі питання визначення обставин, що підлягають доказуванню у кримінальному провадженні щодо застосування примусових заходів медичного характеру - Даниленко, А. В.; Danylenko, A. V.; ORCID: http://orcid.org/0000-0002-7721-2955 (Журнал східноєвропейського права. – 2016. – № 26. - С. 55-59, 2016)
Стаття присвячена вивченню загального поняття предмету доказування у кримінальному провадженні. Також розглянуто спеціальний предмет доказування щодо кримінальних проваджень про застосування примусових заходів медичного характеру. Визначені конкретні обставини, які підлягають доказуванню та надана їх характеристика.

The author of the article emphasizes that achievement of the goal of criminal procedure proof is possible only when sufficient completeness and accuracy will be installed regarding all the circumstances and facts, the totality of which forms the subject of proof. In cases of committing an illegal act by socially dangerous irresponsible person installing all circumstances of proof provided by Criminal Procedure Code creates the possibility of the court to decide on the application of compulsory medical measures to a specific person. According to the provisions of the current Criminal Procedure Code of Ukraine subject of proof in criminal proceedings establishes Art. 91, so-called “common” item of proof. However, in the criminal procedure science it is adopted to isolate “special” item of proof in certain categories of proceedings. Special items of proof are determined at the level of special rules of Criminal law, which set out specific legal features of committed criminal offenses and regulations of Art. 91 of the Criminal Procedure Code of Ukraine and certain chapters of the Criminal Procedure Code of Ukraine, that regulate the so-called special proceedings. The author of the article emphasizes that clarification of the circumstances according to Art. 505 of the Criminal Procedure Code of Ukraine during criminal proceedings for the application of compulsory medical measures is necessary for the correct application of the law on insane persons and therefore respect their rights and interests. The activities of the investigator shall comply with the established law in order to carry out the collection of evidence during the preliminary investigation, which will be the basis for the court to make legal and fair decision.

Статья посвящена изучению общего понятия предмета доказывания в уголовном производстве. Также рассмотрен специальный предмет доказывания по уголовным производствам о применении принудительных мер медицинского характера. Определены конкретные обстоятельства, которые подлежат доказыванию и предоставлена их характеристика.
Some Aspects of Determining the Circumstances to Be Established during the Preliminary Investigation in the Criminal Proceedings on Application of Compulsory Medical Measures
Даниленко А. В. Про окремі питання визначення обставин, що підлягають доказуванню укримінальному провадженні щодо застосування примусових заходів медичного характеру [Електронний ресурс] / Даниленко Анастасія Володимирівна // Журнал східноєвропейського права: електронне науково-практичне фахове видання. – 2016. – № 26. - С. 55-59. - Режим доступу: http://easternlaw.com.ua/uk/arxiv-nomerov/zhurnal-sxidnoyevropejskogo-prava-26.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; предмет доказування; кримінальне провадження; неосудна особа; примусові заходи медичного характеру; subject of proof; criminal proceedings; irresponsible person; compulsory measures of a medical nature; предмет доказывания; уголовное производство; невменяемое лицо; принудительные меры медицинского характера